Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
x + ( 9 - 8 + 7 - 6 + 5 - 4 + 3 ) = 90,28
x + 6 = 90,28
x = 90,28 - 6
x = 84,28
\(a,\frac{7+x}{12}=\frac{2}{3}\)
\(=>7+x.3=12.2\)
\(3\left(7+x\right)=24\)
\(\left(7+x\right)=24:3\)
\(7+x=8\)
\(x=8-7\)
\(x=1\)
\(b,\frac{25-x}{8}=\frac{1}{2}\)
\(25-x.2=8.1\)
\(2\left(25-x\right)=8\)
\(25-x=8:2\)
\(25-x=4\)
\(x=25-4\)
\(x=21\)
x + ( 9 - 8 + 7 - 6 + 5 - 4 + 3 ) = 90,28
x + 6 = 90,28
x = 90,28 - 6
x = 84,28
x + ( 9 - 8 + 7 - 6 + 5 - 4 + 3 ) = 90,28
x + 6 = 90,28
x = 90,28 - 6
x = 84,28
x + ( 9 - 8 + 7 - 6 + 5 - 4 + 3 ) = 90,28
x + 6 = 90,28
x = 90,28 - 6
x = 84,26
x + ( 9 - 8 + 7 - 6 + 5 - 4 + 3 ) = 90,28
x + 6 = 90,28
x = 90,28 - 6
x = 90,28
\(x+\frac{15}{7}=\frac{9}{2}\)
\(x=\frac{9}{2}-\frac{15}{7}=\frac{33}{14}\)
\(x-\frac{3}{4}=\frac{7}{2}\)
\(x=\frac{7}{2}+\frac{3}{4}=\frac{17}{4}\)
\(x.\frac{7}{8}=\frac{12}{5}\)
\(x=\frac{12}{5}:\frac{7}{8}=\frac{96}{35}\)
\(\frac{5}{6}:x=\frac{4}{3}\)
\(x=\frac{5}{6}:\frac{4}{3}=\frac{5}{8}\)
- a) x=9/2-15/7=33/14
- b) x=7/2+3/4=17/4
- c) x=12/5:7/8=61/35
- d) x=5/6:4/3=5/8
- k nha